Education background and monthly household income are factors affecting the knowledge, awareness and practice on haze pollution among Malaysians - Low, Bin-Seng; Selvaraja, Kumaran Ganesh; Ong, Tze-Han; Ong, King-Kok; Koshy, Shajan (Environmental science and pollution research international, 2020)
Transboundary haze pollution caused by periodic forest fires has initiated a serious negative implication to the economy, tourism sectors and public health in Southeast Asia. Due to the raising concerns of health effects of haze towards the Malaysian population, the present study was conducted to investigate the degree of awareness towards haze and the number of safety measures adopted by the Malaysian population during the haze crisis based on demographic characteristics. A cross-sectional questionnaire-based study was conducted from 4 to 29 January 2016 on 387 subjects in Klang Valley, Malaysia. The results showed that more than 90% of the respondents were aware of the hazards of haze pollution. Respondents with higher education background with diploma, undergraduate and postgraduate degree possessed greater awareness on the hazards of haze ( p < 0.001) and practiced safety measures ( p = 0.025) compared with those with lower education background with no proper schooling, primary schooling and secondary schooling. Among the subjects with higher household income (>RM 10,000/month) had higher awareness level on haze ( p < 0.05) and adopted more safety measures ( p < 0.05) compared with respondents with lower household income (<RM 3000/month). Despite controversies regarding the association of demographic factors with awareness level on haze reported, our present study confirmed that demographic factors such as the education background and monthly household income are affecting the awareness score and the number of safety measure taken during haze episode in Malaysia. Hence, more awareness on haze pollution to engage more safety measures during haze episodes should address to the lower education level and socioeconomic group to improve their health and quality of life.